1977
DOI: 10.1136/jnnp.40.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical responses in the platysma and in the adductor pollicis muscle: in patients with myasthenia gravis.

Abstract: SUMMARY Electrical and mechanical muscular responses to single and repetitive stimuli were recorded in 24 patients with myasthenia gravis. Findings in the platysma were compared with those in m. adductor pollicis (ADP). In the platysma, but not in the ADP, electrical and mechanical responses to single stimuli were often lower than normal, and could be normalised after tetanus and by edrophonium. The decrement of electrical and mechanical responses to repetitive stimuli was two to three times greater in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The PTF was larger in the platysma than in the ADP (Krarup 1977b) and similar in the elbow flexors and the ADP (Horowitz . This difference may be related to the fact that the amplitude of the action potential evoked before the tetanus was lower than normal in 10 of 24 patients in the platysma whereas it was within the normal range in the ADP ( Krarup 1977b and the elbow flexors of 31 patients (Horowitz . The rate of decay of the PTF was faster than that of the PTP and had disappeared 10-20 s after the tetanus (Krarup 1977b, Fig.…”
Section: Post-tetan Ic Faci I Itationmentioning
confidence: 96%
See 1 more Smart Citation
“…The PTF was larger in the platysma than in the ADP (Krarup 1977b) and similar in the elbow flexors and the ADP (Horowitz . This difference may be related to the fact that the amplitude of the action potential evoked before the tetanus was lower than normal in 10 of 24 patients in the platysma whereas it was within the normal range in the ADP ( Krarup 1977b and the elbow flexors of 31 patients (Horowitz . The rate of decay of the PTF was faster than that of the PTP and had disappeared 10-20 s after the tetanus (Krarup 1977b, Fig.…”
Section: Post-tetan Ic Faci I Itationmentioning
confidence: 96%
“…1968). We studied similar phenomena in proximal muscles (Krarup 1977b. For comparison we studied twitch potentiation in muscular dystrophy and other myopathies without abnormalities in neuromuscular transmission .…”
mentioning
confidence: 99%
“…2,16,19,22 Twelve hours was recommended as the length of time to withhold the medications. 16,19 One study did withhold medications from 4 to 18 h. 16,22 For LEMS, it was suggested that a screening test be performed to determine if RNS or SFEMG is needed. This involved recording and comparing a single pre-and postexercise supramaximal CMAP for differences in amplitude.…”
Section: Resultsmentioning
confidence: 99%
“…Krarup 16 compared RNS in a proximal muscle (platysma) to a distal muscle (adductor pollicis) in 24 patients with MG. He found that the decrement in the platysma with RNS was two to three times greater than in the adductor pollicis.…”
Section: Repetitive Nerve Stimulation Repetitive Nerve Stimulation Imentioning
confidence: 99%
See 1 more Smart Citation